Coupling element-based dual-antenna structures for mobile terminal with hand effects - Abdullah Al-Hadi, Azremi; Ilvonen, Janne; Valkonen, Risto; Holopainen, Jari; Kivekäs, Outi; Icheln, Clemens (Springerlink, 2011)
Link at publisher's homepage at http://www.springerlink.com/